Inelastic response of thermo-oxidatively aged carbon black filled polychloroprene rubber. Part II: Mullins effect. (October 2022) - Kittur, M.I.; Andriyana, A.; Ang, B.C.; Ch'ng, S.Y.; Verron, E.
Highlights: Part I Thermo-oxidative (TO) aging causes evolution of crosslinks and chain scissions. Evolution of elastomer network significantly affects the stress relaxation behavior. Multi-step loading causes strain-induced crystallization that is strongly affected by TO aging. Maxwell-Weichert model is used to predict the time to reach the state of equilibrium. Part II The effect of thermo-oxidative aging on Mullins effect is investigated. Mullins softening increases with thermo-oxidative aging durations. The evolution of elastomer network significantly affects the Mullins effect and its recovery. Abstract: The present investigation focuses on the effect of the elastomer network modifications in the elastomer network due to thermo-oxidative aging (as proposed in Part I) on the Mullins effect. A series of cyclic mechanical tensile loading modes are imposed on thermo-oxidatively aged specimens to understand the repercussions of crosslinking and chain scission on Mullins effect and its recovery. Mullins effect is characterized using two methods to assess the stress-softening occurring as a result of thermo-oxidative aging. The observations reveal that hysteresis, permanent set, Mullins effect, and its recovery are significantly affected by the change in elastomer network.